Interobserver Agreement of FOLR1 Immunohistochemistry in Gynecologic Carcinomas: A Multi-Institutional Study - Na Niu; Sara Salehiazar; Minhua Wang; Tong Sun; Rita Abi-Raad; Stephanie McGregor; Padmini Manrai; Amy Joehlin; Pei Hui; Natalia Buza (Archives of Pathology & Laboratory Medicine, 2026)
Context.— Mirvetuximab soravtansine-gynx (MIRV), a new antibody-drug conjugate, is approved by the US Food and Drug Administration for folate receptor alpha (FOLR1)–positive, platinum-resistant ovarian carcinoma, and clinical trials for its use in endometrial cancer are currently underway. The current clinical cutoff for FOLR1 positivity is at least 75% of viable tumor cells with moderate and/or strong membranous staining intensity, although national treatment guidelines also recommend MIRV for recurrent ovarian carcinomas with staining cutoffs of 50% or greater and 25% or greater in certain circumstances; and endometrial carcinomas with lower cutoffs may be eligible for clinical trials. Objective.— To assess the reproducibility of FOLR1 interpretation at different scoring cutoffs in correlation with the clinicopathologic characteristics. Design.— Forty consecutive gynecologic carcinomas with available FOLR1 status were retrieved from our archives to include 20 FOLR1-positive and 20 FOLR1-negative cases. Hematoxylin-eosin– and FOLR1-immunostained slides were individually evaluated by 8 pathologists, blinded to the original clinical FOLR1 result. Statistical analysis was performed with SAS software. Results.— The study cohort included 31 tubo-ovarian, 7 endometrial, and 2 Müllerian carcinomas with uncertain primary sites. Complete agreement of FOLR1 status among all observers with staining cutoffs of 75%, 50%, and 25% was achieved in 29 (κ = 0.77), 31 (κ = 0.81), and 32 (κ = 0.81) cases, respectively. Using the 75% cutoff, the overall agreement rate was significantly lower in postchemotherapy samples than in untreated tumors: 57% (13 of 23) versus 94% (16 of 17), respectively ( P = .009). Conclusions.— FOLR1 scoring is highly reproducible in gynecologic carcinomas. However, disagreements exist, especially in the postchemotherapy setting, and may significantly impact the treatment eligibility.